Key Elements of Failure of the Enterprises Operated by the Women Entrepreneurs - Swetha.M , Jagan Mohan Reddy.M , Sudharani.V (Indian Journal of Extension Education, 2015)
Women’s entrepreneurship is both about women’s position in society and about the role of entrepreneurship in the same society. Women entrepreneurs faced many obstacles specifically in marketing their products (including family responsibilities) that have to be overcome in order to give them access to the same opportunities as men. Empowerment among women makes them to join in the mainstream of development. Hence the present paper focused on analyzing the key elements of failure of the enterprises operated by the women entrepreneurs. The elements contributed for the failure of women enterprises are heavy competition, lack of advertisement for the product, lack of remunerative price for the product in the market, insufficient working capital and seasonal demand for the product in various enterprises.